2002
DOI: 10.1021/jf0255331
|View full text |Cite
|
Sign up to set email alerts
|

Seed Composition of Soybeans Grown in the Harran Region of Turkey As Affected by Row Spacing and Irrigation

Abstract: This study was conducted to determine the effects of row spacing (RS) and irrigation (IR) on protein content, oil content, and fatty acid composition of soybeans grown in the Harran region of Turkey. Oil content of the seed varied from 20.9 to 22.3%. Oil and protein contents were both affected by year. RS and IR affected protein and oil contents significantly (P < 0.01) in both years. RS of 70 cm had the highest protein content, followed by RS of 60, 40, and 50 cm, respectively. IR every 3rd day resulted in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 14 publications
6
87
4
Order By: Relevance
“…The level of linoleic acid found in the current study was higher than previous reported values ( Boydak et al, 2002), oleic acid level, however, was lower. Conversely, the results are consistent with the findings of Celik (1995), except for palmitic acid.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The level of linoleic acid found in the current study was higher than previous reported values ( Boydak et al, 2002), oleic acid level, however, was lower. Conversely, the results are consistent with the findings of Celik (1995), except for palmitic acid.…”
Section: Discussioncontrasting
confidence: 95%
“…It is considered as a good source of high quality plant protein and vegetable oil. Given its high concentration of protein (36-48%), oil (18-24%), and carbohydrate (20%), soybean is grown in almost all parts of the world for human consumption, industry and animal feed (Arıoglu, 1989;Boydak et al, 2002). Besides, diets including soybean have been proposed to reduce risk of major diseases such as breast cancer, cardiovascular disease, osteoporosis, diabetes and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Protein and oil analyses were based on a seed dry matter basis [50,51], and fatty acids were analyzed based on an oil basis.…”
Section: Growth Conditions and Experimental Designmentioning
confidence: 99%
“…These authors suggest that by monitoring the minimum temperatures and the daily increase during the seed filling period might have predictive value for seeds oil concentration. It has been informed that not only the high temperatures but also the presence of water stress during the filling of seeds produces alterations in the contents of proteins and oils (Boydak et al, 2002). It is also frequently found a negative relationship between seed protein content and crop yield (Shannon et al, 1972;Yin & Vyn, 2005); moreover, there are evidences of a negative correlation between oils and proteins concentration.…”
Section: Aba Promotes Yield In Field-cultured Soybeanmentioning
confidence: 99%